Risk Sexual Behaviour In Students Aged 12-18 - Nevena Tzvetanova; Joana Simeonova; Yanka Tzvetanova (Journal of Biomedical & Clinical Research, 2014)
The aim of this study was to identify risk sexual behavior in students aged 12-18 in Veliko Turnovo region. A cross-sectional study was carried-out in 2014. Three hundred and ten students attending seven schools filled in a self-administered questionnaire. The questionnaire included 48 questions, sixteen of which collected information about sexual behaviour, regarding contraception, casual sex with different partners, sexually transmitted diseases (STD), hygiene after sex, etc. The data were processed with SPSS.v.19. Parametric and non-parametric statistical methods were applied. Over 50% of the students reported being sexually active, most of them since they turned 16. Almost half of the respondents had had casual sexual partners and 46 percent had had sex within a week after initiation of a new relationship. Less than one third of the students reported safe sex behaviour. Seven percent of the students had a history of STDs, and one in six did not practice proper hygiene after sex. Identification of all aspects of risk sexual behavior in students aged 12-18 provides an opportunity to study the problem systematically and comprehensively. Planning and implementation of effective health education programs in schools require the application of an integrated approach with the participation of students, teachers, parents, health professionals and policy makers.